Literasi Digital Sebagai Peningkatan Pemahaman Masyarakat Dengan Door To Door dan Seminar - Setiawan, Ridwan; Tata, Muhammad; Siedik, Nizar Khoerul Anam; Sundari, Ayu; Yulistiani, Sri; Nursifa, Fadia Siti; Nurhidayanti, Shopi; Rohayani, Siti; Azwardhi, Miftah Yuzar; Buchori, Nizar; Rifaldi, Muhammad; Saifurrahman, Saifurrahman; Putra, Raka Septyan; Ardiansyah, Rifky; Hakim, Lutfi Lukmanul; Ibrahim, Muhamad Faisal Juliana; Nugraha, Daffa; Nurhidayati, Salma; Agustin, Novi Yuliani; Ireland, Nova Audi (Jurnal PkM MIFTEK, 2023)
Digital literacy KKN activities in villages are an alternative choice offered by the Ministry of Communication and Informatics to tertiary institutions in order to accelerate development in villages and improve the quality of human resources in villages through digital use. The purpose of this service is to carry out digital literacy in the community as a support for the work program of the Ministry of Communication and Information with a minimum target of 500 literate people using the method of conducting seminars and door to door to residents directly. The results of the post test showed that the material was: Digitizing Culture and ICT, namely 94.00, from the Digital Citizenship material, it was 96.80 and from the material Getting to Know Digital Wallets, Marketplaces, and Transactions, it was 96.70.